Класифікація персоналу Державного бюро розслідувань України (на основі аналізу його штатно-організаційної структури) - Чишко, К. О.; Chyshko, K. O.; Чишко Катерина Олександрівна (Вісник Кримінологічної асоціації України. – 2023. – № 30(3). – С. 382-389, 2023)
У статті запропоновано авторське бачення класифікації персоналу Державного бюро розслідувань за наступними кретеріями: професійна приналежність, тобто конкретним видом трудової діяльності, здійснення якого потребує кваліфікації, сукупності теоретичних і практичних навичок та/або спеціалізації (юристи, правоохоронці, економісти, інженери, психологи і.т.д.); рівень кваліфікації, який визначає ступінь готовності співробітника до виконання професійних функцій і залежить від наявності чи відсутності дипломів про освіту, підвищення кваліфікації, досвіду роботи (висококваліфіковані, кваліфіковані, малокваліфіковані та некваліфіковані); посадове становище (директор, перший заступник директора, заступники директора, керівники управлінь і їх заступники, начальники відділів і їх заступники, детективи, старші оперуповноважені та оперуповноважені, інспектори тощо); правове становище в системі управління: посадові особи, представники влади, робітники тощо; функціональний напрям професійної діяльності (керівний склад, спеціалісти, службовці, робітники і.т.п.).

The article proposes the author's vision of the classification of the personnel of the State Bureau of Investigation according to the following criteria:professional affiliation, i.e. a specific type of work, the implementation of which requires qualifications, a set of theoretical and practical skills and/or specialization (lawyers, law enforcement officers, economists, engineers, psychologists, etc.). etc.); the level of qualification, which determines the degree of readiness of the employee to perform professional functions and depends on the presence or absence of diplomas on education, advanced training, work experience (highly qualified, qualified, low-qualified and unqualified); position (director, first deputy director, deputy directors, heads of departments and their deputies, heads of departments and their deputies, detectives, senior operational officers and operational officers, inspectors, etc.); legal position in the management system: officials, government representatives, workers, etc.; functional direction of professional activity (management, specialists, employees, workers, etc.). Also, based on the characteristics of the organizational and staff structure of the State Bureau of Investigation and the division carried out, its staff (in a broad sense) is defined as a set of persons who, on a permanent or temporary basis, undergo state (public) service, performing professional activities in the central apparatus, its territorial offices , as well as other institutions of the State Bureau of Investigation and will receive financial support or wages for this (if they work under the terms of a tour contract).

В статье предложено авторское видение классификации персонала Государственного бюро расследований.
Keywords: публічні службовці; державна служба; публічна служба; персонал; кадри; Державне бюро розслідувань; державні службовці; проходження служби; State Bureau of Investigation; public service; personnel; public servants; service; Ukraine; Украина; Україна; государственная служба